Strategi Pengembangan Wilayah Berbasis Ekonomi Lokal Melalui Sektor Perikanan Di Kelurahan Mamboro Barat Kecamatan Palu Utara - Danuharsa, Agung Ayu Ratih; Rizkhi; Rusli; Akhmad, Abdul Gani; Lutfi (Prodi PWK Universitas Tadulako, 2025)
West Mamboro Village, which is located in North Palu District with an area of 6.05 km², has significant potential for the fisheries sector. This research aims to identify the potential of the fisheries sector, analyze the relationship between the local economy and regional development, and formulate a development strategy based on the local economy through the fisheries sector. The method used is Mix Methods, using correlation analysis and multiple regression to determine the relationship and influence of natural resources, human resources, artificial resources, and local economic variables on the variables of regional development strategies based on the local economy of the fisheries sector, as well as SWOT analysis to determine the strategy of the variables that are influential and have a relationship. The results of the study show in the multiple correlation and regression analysis that the variables of natural resources, human resources, artificial resources, local economy are influential, and the SWOT analysis produces comprehensive strategies, such as capacity building through training, diversification of fishery businesses, strengthening access to capital and technology, preservation of the marine environment, adoption of modern technology, improvement of product quality, development of disaster-resistant infrastructure, and development of marketing systems competitive ones. This strategy aims to create a sustainable and inclusive development ecosystem, as well as attract the younger generation to the fisheries sector. The conclusion of this study confirms that the potential of the fisheries sector in West Mamboro Village is the key to local economic development and fishermen's welfare, with sustainable management needed to maintain a healthy marine ecosystem.